Maternal nutrition in pregnancy and metabolic risks among neonates in a Pakistani population, a pilot study. (11th May 2015) - Shaikh, F.; Basit, A.; Hakeem, R.; Fawwad, A.; Hussain, A.
Abstract : The aim of this study was to observe the association between maternal undernutrition and metabolic risk indicators in newborns at birth. Fifty-nine expectant mothers between 28 and 40 weeks of gestation were included after obtaining their informed consent. Mothers were divided into undernourished, normally nourished and overnourished groups. A total of 54 deliveries were followed-up, and cord blood samples were collected. Metabolic status at birth was assessed by determining the cord blood concentrations of glucose, insulin and lipids and by measuring insulin resistance through homeostasis model assessment. Metabolic risk indicators in the offspring were compared following mothers' nutrition status (under and normal nourished groups). We found that concentrations of glucose (5.31±2.01 v . 4.69±2.22 mmol/l, P =0.01), total cholesterol (2.51±1.52 v . 1.84±0.66 mmol/l, P =0.04), triglycerides (0.85±1.12 v . 0.34±0.24 mmol/l, P =0.00) and low-density lipoprotein (LDL)-cholestrol (1.26±0.93 v . 1.02±0.50 mmol/l, P =0.04) were significantly high in the offspring born to undernourished mothers. LDL-cholestrol remained significantly high in the undernourished group even after adjustment for potential confounders. Furthermore, a weak association was observed between maternal body fat mass with serum leptin ( r =0.272, P =0.05) and maternal body mass Index with LDL-cholestrol in the cord blood ( r =0.285, P =0.05). Our results showed that offspring of undernourished mothers had a relatively higher metabolic risk profile including LDL-cholestrol compared with normal nourished group, suggesting that maternal undernutrition may influence metabolic risk markers of the newborn at birth. We recommend that these results should be confirmed by a longitudinal study with a larger sample size.